The Role of Copper Intake in Bone Health: A Quantitative Analysis in Postmenopausal Spanish Women - María Luz Canal-Macías; Luis Manuel Puerto-Parejo; Jesús María Lavado-García; Raúl Roncero-Martín; Juan Diego Pedrera-Zamorano; Fidel López-Espuela; Purificación Rey-Sánchez; Antonio Sánchez-Fernández; José M. Morán (European Journal of Investigation in Health, Psychology and Education)
(1) Background: Copper is a crucial trace element which is vital to growth and development and is especially important in bone health. Copper intake is now the focus of much broader research beyond its associations with nail growth, looking at copper’s potential in contributing to bone integrity to prevent a high risk of osteoporosis as well. (2) Methods: This study included postmenopausal women from a larger longitudinal study conducted between 2019 and 2022. Bone health was assessed using three quantitative techniques: heel QUS, DXA and pQCT. Copper intake was evaluated using a 131-item, 7-day food frequency questionnaire. Data from these assessments were used to analyze the relationship between copper intake and bone health. (3) Results: In the unadjusted multiple linear regression model, associations were found between copper intake levels and both BUA (dB/MHz) and pQCT cortical + subcortical density (mg/cm3), with copper intake acting as a negative predictor in both instances. However, these associations lost statistical significance after adjusting for participant age and weight. No further associations were identified for the other parameters assessed. (4) We conclude that our study does not reveal an association between copper intake and bone health in postmenopausal Spanish women.